2015
DOI: 10.1007/s13361-015-1192-0
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Disaccharide Isomers by Temperature-Dependent In-Source Decay (TDISD) and DART-Q-TOF MS/MS

Abstract: Abstract. Helium direct analysis in real time (He-DART) mass spectrometry (MS) of some compounds, polysaccharides, for example, usually tends to be challenging because of the occurrence of prominent in-source decay (ISD), which was considered as an undesired side reaction, as it complicated the resulting mass spectra. Our approach is to take advantage of an efficient and practical method termed the temperature-dependent ISD (TDISD) technique combined with fragmentation of the dehydrated dimers using DART Q-TOF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…S2 in SI. DART can generate radical, cluster or/and protonated/deprotonated ions [33,45], however, ammonium adduct is common for carbohydrates via DART ionization according to literature studies [4650]. For example, m/z 198 is identified as ammonium adduct of monosaccharide in positive mode, [M + NH 4 ] + ; ions of m/z 180 were confirmed to be ammonium adduct of water loss product from hexose [M + NH 4 -H 2 O] + ; m/z values of 163, 145, 127 are protonated ions resulted from series of water loss from hexose as annotated (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…S2 in SI. DART can generate radical, cluster or/and protonated/deprotonated ions [33,45], however, ammonium adduct is common for carbohydrates via DART ionization according to literature studies [4650]. For example, m/z 198 is identified as ammonium adduct of monosaccharide in positive mode, [M + NH 4 ] + ; ions of m/z 180 were confirmed to be ammonium adduct of water loss product from hexose [M + NH 4 -H 2 O] + ; m/z values of 163, 145, 127 are protonated ions resulted from series of water loss from hexose as annotated (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Figure 2 With the investigation of various monosaccharide standards with DART-MS, it was found that the pyrolysis fragmentation pattern of polysaccharide is not the simple addition of the mass peaks from different monomers. 31,33,34 The direct thermal decomposition of large saccharides using DART source is different from the traditional controlled acid hydrolysis, and its detailed cleavage pathway is not clear yet. The small fragments generated from DART-MS can reveal the structural diversity of polysaccharides somewhat, but it is probably not adequate for the structure elucidation of polysaccharide macromolecules.…”
Section: Dart-ms Analysis Of Polysaccharidesmentioning
confidence: 99%
“…59,64,66 Applications adjusting the DART gas heater temperature have been used to characterize pyrolysis product evolution, 67-69 complex sample differentiation, [70][71][72] and to induce fragmentation of known molecules at higher temperatures (150-400 C). [73][74][75] Additionally, temperature programmed desorption (TPD) has been used in petroleomics studies with success at helping to simplify analysis. 65 Using the EZ-DART source we examined the TPD analysis of a PPG sample (described in the ESI †) and a viscous liquid asphalt, shown here, demonstrating that methods requiring DART heater adjustment can be used with the EZ-DART source.…”
Section: Tpd Based Experimentsmentioning
confidence: 99%